Disentangling the effect of farming practice from aridity on crop stable isotope values: A present-day model from Morocco and its application to early farming sites in the eastern Mediterranean. (April 2016) - Styring, Amy K; Ater, Mohammed; Hmimsa, Younes; Fraser, Rebecca; Miller, Holly; Neef, Reinder; Pearson, Jessica A; Bogaard, Amy
Agriculture has played a pivotal role in shaping landscapes, soils and vegetation. Developing a better understanding of early farming practices can contribute to wider questions regarding the long-term impact of farming and its nature in comparison with present-day traditional agrosystems. In this study we determine stable carbon and nitrogen isotope values of barley grains from a series of present-day traditionally managed farming plots in Morocco, capturing a range of annual rainfall and farming practices. This allows a framework to be developed to refine current isotopic approaches used to infer manuring intensity and crop water status in (semi-)arid regions. This method has been applied to charred crop remains from two early farming sites in the eastern Mediterranean: Abu Hureyra and 'Ain Ghazal. In this way, our study enhances knowledge of agricultural practice in the past, adding to understanding of how people have shaped and adapted to their environment over thousands of years.